Structure–Function Study of a Novel Inhibitor of Cyclin-Dependent Kinase C in Arabidopsis. (31st August 2022) - Saito, Ami N; Maeda, Akari E; Takahara, Tomoaki T; Matsuo, Hiromi; Nishina, Michiya; Ono, Azusa; Shiratake, Katsuhiro; Notaguchi, Michitaka; Yanai, Takeshi; Kinoshita, Toshinori; Ota, Eisuke; Fujimoto, Kazuhiro J; et al.
Abstract: The circadian clock, an internal time-keeping system with a period of about 24 h, coordinates many physiological processes with the day–night cycle. We previously demonstrated that BML-259 [ N -(5-isopropyl-2-thiazolyl) phenylacetamide], a small molecule with mammal CYCLIN DEPENDENT KINASE 5 (CDK5)/CDK2 inhibition activity, lengthens Arabidopsis thaliana (Arabidopsis) circadian clock periods. BML-259 inhibits Arabidopsis CDKC kinase, which phosphorylates RNA polymerase II in the general transcriptional machinery. To accelerate our understanding of the inhibitory mechanism of BML-259 on CDKC, we performed structure–function studies of BML-259 using circadian period-lengthening activity as an estimation of CDKC inhibitor activity in vivo. The presence of a thiazole ring is essential for period-lengthening activity, whereas acetamide, isopropyl and phenyl groups can be modified without effect. BML-259 analog TT-539, a known mammal CDK5 inhibitor, did not lengthen the period nor did it inhibit Pol II phosphorylation. TT-361, an analog having a thiophenyl ring instead of a phenyl ring, possesses stronger period-lengthening activity and CDKC;2 inhibitory activity than BML-259. In silico ensemble docking calculations using Arabidopsis CDKC;2 obtained by a homology modeling indicated that the different binding conformations between these molecules and CDKC;2 explain the divergent activities of TT539 and TT361.